Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure! Let's solve this step by step.
The general equation for a circle in the coordinate plane with the center [tex]\((h, k)\)[/tex] and radius [tex]\(r\)[/tex] is given by:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
Here, the center of the circle is given as [tex]\((-6, -8)\)[/tex]. Substituting [tex]\(h = -6\)[/tex] and [tex]\(k = -8\)[/tex] into the general equation, we get:
[tex]\[ (x + 6)^2 + (y + 8)^2 = r^2 \][/tex]
Next, we need to determine the radius [tex]\(r\)[/tex]. To do this, we use the point [tex]\((0, -8)\)[/tex], which lies on the circle.
Substitute [tex]\(x = 0\)[/tex] and [tex]\(y = -8\)[/tex] into the equation:
[tex]\[ (0 + 6)^2 + (-8 + 8)^2 = r^2 \][/tex]
This simplifies to:
[tex]\[ 6^2 + 0^2 = r^2 \][/tex]
[tex]\[ 36 + 0 = r^2 \][/tex]
[tex]\[ r^2 = 36 \][/tex]
So, the equation of the circle is:
[tex]\[ (x + 6)^2 + (y + 8)^2 = 36 \][/tex]
Among the given options, we must find the equation that matches this form. The options are:
1. [tex]\((x-6)^2 + (y-8)^2 = 6\)[/tex]
2. [tex]\((x-6)^2 + (y-8)^2 = 36\)[/tex]
3. [tex]\((x+6)^2 + (y+8)^2 = 6\)[/tex]
4. [tex]\((x+6)^2 + (y+8)^2 = 36\)[/tex]
The correct option is:
[tex]\[ (x + 6)^2 + (y + 8)^2 = 36 \][/tex]
Therefore, the correct answer is the fourth option:
[tex]\[ (x+6)^2 + (y+8)^2 = 36 \][/tex]
The general equation for a circle in the coordinate plane with the center [tex]\((h, k)\)[/tex] and radius [tex]\(r\)[/tex] is given by:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
Here, the center of the circle is given as [tex]\((-6, -8)\)[/tex]. Substituting [tex]\(h = -6\)[/tex] and [tex]\(k = -8\)[/tex] into the general equation, we get:
[tex]\[ (x + 6)^2 + (y + 8)^2 = r^2 \][/tex]
Next, we need to determine the radius [tex]\(r\)[/tex]. To do this, we use the point [tex]\((0, -8)\)[/tex], which lies on the circle.
Substitute [tex]\(x = 0\)[/tex] and [tex]\(y = -8\)[/tex] into the equation:
[tex]\[ (0 + 6)^2 + (-8 + 8)^2 = r^2 \][/tex]
This simplifies to:
[tex]\[ 6^2 + 0^2 = r^2 \][/tex]
[tex]\[ 36 + 0 = r^2 \][/tex]
[tex]\[ r^2 = 36 \][/tex]
So, the equation of the circle is:
[tex]\[ (x + 6)^2 + (y + 8)^2 = 36 \][/tex]
Among the given options, we must find the equation that matches this form. The options are:
1. [tex]\((x-6)^2 + (y-8)^2 = 6\)[/tex]
2. [tex]\((x-6)^2 + (y-8)^2 = 36\)[/tex]
3. [tex]\((x+6)^2 + (y+8)^2 = 6\)[/tex]
4. [tex]\((x+6)^2 + (y+8)^2 = 36\)[/tex]
The correct option is:
[tex]\[ (x + 6)^2 + (y + 8)^2 = 36 \][/tex]
Therefore, the correct answer is the fourth option:
[tex]\[ (x+6)^2 + (y+8)^2 = 36 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.